Importancia de la dieta en pacientes diabéticos - Díaz G., Emma; Riffo M., Andrea (Revista Hospital Clínico Universidad de Chile, 2012)
A proper diet plan is essential for the successful care and managing of type 2 diabetes. The goals of treatment are to achieve and maintain a normal body weight, glycated hemoglobin below 7, normal blood lipid levels, prevent acute complications and reduce the risk of developing long-term complications. Bariatric surgery is a therapeutic alternative for patients with moderate or morbid obesity and type 2 diabetes. Before surgery it is important to promote the correction of eating habits, improve metabolic control and inform the patient about the postoperative process. Inmediately after surgery the goals are to protect and ensure proper healing of the sutures, avoid distension of the gastric reservoir, ensure adequate hydration and prevent the occurrence of gastrointestinal symptoms. After this stage the goals are to adjust feeding to anatomical and physiological changes in the digestive system, evaluate digestive tolerance, monitor weight loss, control biochemical parameters and prevent deficiency states with supplementation of vitamins and minerals. Long term objectives are to prevent deficiency states, control of biochemical parameters and mineral bone density and maintaining weight loss.